Bootstrap pada analisis regresi =Bootstrap on Regression Analysis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRACT Considered a regression model Y(n) = X(n)I3 + s(n), where 13 is a pxl vektor of unknown parameters